Can polylactic acid be a CAD/CAM material for provisional crown restorations in terms of fit and fracture strength? - Benli, Merve; Eker-Gumus, Beril; Kahraman, Yusuf; Huck, Olivier; Ozcan, Mutlu (JAPANESE SOC DENTAL MATERIALS DEVICES, 2021)
This study aimed to evaluate polylactic acid (PLA) as a provisional crown material. Lower right first molar phantom tooth was used for the fabrication of 60 crowns. Samples were divided into three groups (n=20) according to the material: Group PL (PLA), Group PM (polymethyl methacrylate), and Group PE (polyetheretherketone). Each group was investigated for internal and marginal fit, fracture strength, and fracture mode. Data were analyzed using ANOVA, chi-squared test, and Tukey's tests (p=0.05). The average marginal gap value of each group was: PE 56.00 +/- 4.67 mu m, PM 61.15 +/- 4.44 mu m, and PL 60.40 +/- 2.85 mu m (p<0.001). The average internal gap value for each group was: PE 128.90 +/- 8.39 mu m, PM 132.40 +/- 7.51 mu m, and PL 130.75 +/- 9.76 mu m (p=0.442). The average fracture strength of each group was: PE 840.90 +/- 13.23 N, PM 733.30 +/- 9.00 N, and PL 664.50 +/- 10.79 N (p<0.001). Results demonstrated that PLA may be a good option as a provisional crown material.
Keywords: Poly(lactide); Polyetheretherketone; Polymethyl methacrylate; Crowns; IN-VITRO; INTERNAL FIT; ADAPTATION; ACCURACY; RESISTANCE; PLA; Dentistry, Oral Surgery & Medicine; Materials Science